Increasing brain serotonin corrects CO2 chemosensitivity in methyl‐CpG‐binding protein 2 (Mecp2)‐deficient mice. Issue 3 (20th February 2013) - Toward, Marie A.; Abdala, Ana P.; Knopp, Sharon J.; Paton, Julian F. R.; Bissonnette, John M.
<x xml:space="preserve">Abstract</x> Mice deficient in the transcription factor methyl‐CpG‐binding protein 2 (Mecp2), a mouse model of Rett syndrome, display reduced CO2 chemosensitivity, which may contribute to their breathing abnormalities. In addition, patients with Rett syndrome and male mice that are null for Mecp2 show reduced levels of brain serotonin (5‐HT). Serotonin is known to play a role in central chemosensitivity, and we hypothesized that increasing the availability of 5‐HT in this mouse model would improve their respiratory response to CO2. Here we determined the apnoeic threshold in heterozygous Mecp2‐deficient female mice and examined the effects of blocking 5‐HT reuptake on the CO2 response in Mecp2‐null male mice. Studies were performed in B6.129P2(C)‐Mecp2τm1.1Bird null males and heterozygous females. In an in situ preparation, seven of eight Mecp2‐deficient heterozygous females showed arrest of phrenic nerve activity when arterial CO2 was lowered to 3%, whereas the wild‐types maintained phrenic nerve amplitude at 53 ± 3% of maximal. In vivo plethysmography studies were used to determine CO2 chemosensitivity in null males. These mice were exposed sequentially to 1, 3 and 5% CO2. The percentage increase in minute ventilation in response to increased inspired CO2 was less in Mecp2−/y than in Mecp2+/y mice. Pretreatment with citalopram, a selective 5‐HT reuptake inhibitor (2.5 mg kg−1 i.p.), 40 min prior to CO2 exposure, in Mecp2−/y mice resulted in an improvement in CO2 chemosensitivity to wild‐type levels. These results suggest that decreased 5‐HT in Mecp2‐deficient mice reduces CO2 chemosensitivity, and restoring 5‐HT levels can reverse this effect.